2023
DOI: 10.3390/ph16030357
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic-Fermented Camel Milk Attenuates Neurodegenerative Symptoms via SOX5/miR-218 Axis Orchestration in Mouse Models

Abstract: Multiple sclerosis is an autoimmune-mediated myelin damage disorder in the central nervous system that is widespread among neurological patients. It has been demonstrated that several genetic and epigenetic factors control autoimmune encephalomyelitis (EAE), a murine model of MS, through CD4+ T-cell population quantity. Alterations in the gut microbiota influence neuroprotectiveness via unexplored mechanisms. In this study, the ameliorative effect of Bacillus amyloliquefaciens fermented in camel milk (BEY) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Disturbance of the gut-brain axis, a bidirectional relationship between the microbiota in the digestive tract and the brain, has been linked to neuroinflammatory response and neurological disorders [29,30]. Cow milk offers a suitable nutritional medium for many microorganisms, including probiotics, due to its high content of essential molecules including carbohydrates, proteins, lipids, vitamins, and minerals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disturbance of the gut-brain axis, a bidirectional relationship between the microbiota in the digestive tract and the brain, has been linked to neuroinflammatory response and neurological disorders [29,30]. Cow milk offers a suitable nutritional medium for many microorganisms, including probiotics, due to its high content of essential molecules including carbohydrates, proteins, lipids, vitamins, and minerals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Hsp65-producing Lactococcus lactis inhibits experimental autoimmune encephalomyelitis by preventing cell migration into the spinal cord [35]. Furthermore, other probiotic species such as Bacillus amyloliquifaciens-supplemented camel milk suppress the neuroinflammation of autoimmune encephalomyelitis by regulating inflammatory markers [29], as well as by regulating SOX5/miR-218 axis orchestration in mouse models [30]. STAT-3 diminished apoptosis and polarized the OLs in LPS-induced immunogenicity, which resulted in defective regulation of MBP and GFAP in OLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation